Resilience and Stress as Mediators in the Relationship of Mindfulness and Happiness - Bajaj, Badri; Khoury, Bassam; Sengupta, Santoshi (Frontiers in Psychology, 2022)
The aim of the present study was to examine the mediation effects of resilience and stress, two perceived opposite constructs, in the relationship of mindfulness and happiness. Mindful Attention Awareness Scale, Connor–Davidson Resilience Scale, Subjective Happiness Scale, Depression Anxiety Stress Scales short version-21were administered to 523 undergraduate university students in India. Structural Equation Modeling with bootstrapping was applied to test the mediating effects of resilience and stress. Results showed that resilience and stress partially mediated the mindfulness-happiness relationship. In addition, resilience partially mediated the relationship of mindfulness to stress. Findings suggest that mindfulness may play an influential role in enhancing happiness through the mediating effects of resilience and stress.